Melt-Centrifuged (Bi,Sb)2 Te3 Engineering Microstructure toward High Thermoelectric Efficiency - Pan, Yu (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.